Managing risk with insurance and savings: Experimental evidence for male and female farm managers in West Africa - Delavallade, Clara; Dizon, Felipe; Hill, Ruth Vargas; Petraud, Jean Paul (International Food Policy Research Institute, 2015)
While there is a fast-growing policy interest in offering financial products to help rural households manage risk, the literature is still scant as to which products are the most effective. In order to inform gender targeting of rural finance policy, this paper investigates which financial products best improve farmers’ productivity, resilience, and welfare, and whether benefits affect men and women equally. Using a randomized field experiment in Senegal and Burkina Faso, we compare male and female farmers who are offered index-based agricultural insurance with those who are offered a variety of savings instruments. We found that female farm managers were less likely to purchase agricultural insurance and more likely to invest in savings for emergencies, even when we controlled for access to informal insurance and differences in crop choice. We hypothesize that this difference results from the fact that although men and women are equally exposed to yield risk, women face additional sources of life cycle risk—particularly health risks associated with fertility and childcare—that men do not. In essence, the basis risk associated with agricultural insurance products is higher for women. Insurance was more effective than savings at increasing input spending and use. Those who purchased more insurance realized higher average yields and were better able to manage food insecurity and shocks. This suggests that gender differences in demand for financial products can have an impact on productivity, resilience, and welfare.